Healthy eating: A concept analysis - Sh Sugiharto; Chen-Chung Hey; Agus Supinganto; Nilawati Uly (Malahayati International Journal of Nursing and Health Science, 2021)
"Every human being is the creator of his own health or disease (Buddha)". A message of this quote is eat better, health better. Food is an important component and needed by the body to grow and develop as the body fuel. Mistakes in consuming food can be fatal. Therefore, knowledge about healthy eating is needed. Mostly, people refer the term “healthy eating” as a diet. These terms are interchangeable. The term "diet" is defined as restricting the amount of food or avoiding certain foods. Healthy eating is not merely counting the amount of foods, but rather the accuracy of choosing foods based on the need for balanced nutrition. A long with the GERMAS program regarding healthy eating guidelines, namely “Isi Piringku”, then we must understand about food ingredients and their nutritional content as well as balanced nutritional components containing carbohydrates, fats and proteins. The study aimed to construct the concept of healthy eating. The study applied Rodgers’ Evolutionary method for concept analysis. As the results, there are three dimensions of healthy eating involve physical, psychosocial, and biochemistry dimension. By considering these three dimensions of healthy eating, you will eat healthier.